2002
DOI: 10.1038/sj.bjc.6600440
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterisation of six human biliary tract cancer cell lines

Abstract: Human cell lines established from biliary tract cancers are rare, and only five have been reported previously. We report the characterisation of six new six biliary tract cancer cell lines (designated SNU-245, SNU-308, SNU-478, SNU-869, SNU-1079 and SNU-1196) established from primary tumour samples of Korean patients. The cell lines were isolated from two extrahepatic bile duct cancers (one adenocarcinoma of common bile duct, one hilar bile duct cancer), two adenocarcinomas of ampulla of Vater, one intrahepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 23 publications
0
59
1
Order By: Relevance
“…INK4a , hMLH1, CDX1, RASSF1A, and Ecadherin genes, is involved in colorectal carcinogenesis (reviewed by Trojan et al, 2000;Esteller et al, 2001;Ku et al, 2002;Suh et al, 2002;van Engeland et al, 2002). In this study, we analysed the methylation status of the promoter region and performed mutational analysis on the RUNX3 gene in 32 colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…INK4a , hMLH1, CDX1, RASSF1A, and Ecadherin genes, is involved in colorectal carcinogenesis (reviewed by Trojan et al, 2000;Esteller et al, 2001;Ku et al, 2002;Suh et al, 2002;van Engeland et al, 2002). In this study, we analysed the methylation status of the promoter region and performed mutational analysis on the RUNX3 gene in 32 colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal de novo methylation of CpG islands occurs frequently in human cancers including colorectal cancers; moreover, hypermethylation of CpG islands is known to be associated with transcriptional inactivation (Melki et al, 2000;Trojan et al, 2000;Esteller et al, 2001;Song et al, 2001;Zo¨chbauer-Mu¨ller et al, 2001;Ku et al, 2002;Suh et al, 2002;van Engeland et al, 2002;Yang et al, 2002). It has also been reported that transcriptional inactivation by hypermethylation of the promoter region in some genes, for example, APC, LKB1, p16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have evaluated homozygous deletion of the p16 gene in a small series of biliary tract and gallbladder cancer cell lines. Ku et al [25] have reported that homozygous deletion of the p16 gene was detected in three of six (50%) gallbladder cell lines. Yoshida et al [9] have reported that homozygous deletion of the p16 gene was detected in one of two gallbladder cell lines and in two biliary tract cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a frequency of p16 mutation of 0%-80% in gallbladder and biliary tract cancer and cell lines [9,12,14,25] . Ueki et al have reported that 13 of 53 (24.5%) cases of gallbladder cancer showed non-silent p16 gene mutations.…”
Section: Discussionmentioning
confidence: 99%